Ad critique : how to deconstruct ads in order to build better advertising - Tag, Nancy R. (Thousand Oaks, California : SAGE, 2012)
Teaches advertising, marketing, and management students (both the "suits" and the "creatives") how to effectively judge and critique creativity in advertising
1. The case for critique : why we need constructive criticism to make great ads -- 2. AdSpeak : the vocabulary of advertising -- 3. AdErrors : when good ads go bad -- 4. AdAnalogy : how art and copy play together -- 5. The 360 degree critique : being digital, going viral, and beyond -- 6. AdAlliance : your partners in creating great advertising -- 7. AdSpeak up! Who says what when -- 8. The creative team's bill of rights -- 9. The client's bill of rights -- 10. Presentation prep -- 11. Critique cheats : tips to make the most of the critique
Includes bibliographical references and index
Keywords: Advertising; Advertising -- Evaluation; Criticism